2003
DOI: 10.1038/sj.onc.1207091
|View full text |Cite
|
Sign up to set email alerts
|

p53-independent induction of Gadd45 by histone deacetylase inhibitor: coordinate regulation by transcription factors Oct-1 and NF-Y

Abstract: Histone deacetylase (HDAC) inhibitors cause growth arrest at the G1 and/or G2/M phases, and induce differentiation and/or apoptosis in a wide variety of tumour cells. The growth arrest at G1 phase by HDAC inhibitors is thought to be highly dependent on the upregulation of p21/WAF1, but the precise mechanism by which HDAC inhibitors cause G2/M arrest or apoptosis in tumour cells is unknown. Gadd45 causes cell cycle arrest at the G2/M phase transition and participates in genotoxic stress-induced apoptosis. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
96
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 46 publications
11
96
0
Order By: Relevance
“…However, EMSAs showed that TSA treatment did not change the affinity of nuclear factors for the NF-Y or Oct sites in the murine GADD45g promoter (unpublished observations). This agrees with the lack of effect of TSA on the affinity of NF-Y or Oct-1 for their sites in the human GADD45a promoter (Hirose et al, 2003). Alternatively, TSA treatment may affect the interaction of Oct-1 with SMRT-HDAC1, and/or the interactions of NF-Y with HDAC1 or PCAF.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…However, EMSAs showed that TSA treatment did not change the affinity of nuclear factors for the NF-Y or Oct sites in the murine GADD45g promoter (unpublished observations). This agrees with the lack of effect of TSA on the affinity of NF-Y or Oct-1 for their sites in the human GADD45a promoter (Hirose et al, 2003). Alternatively, TSA treatment may affect the interaction of Oct-1 with SMRT-HDAC1, and/or the interactions of NF-Y with HDAC1 or PCAF.…”
Section: Discussionsupporting
confidence: 85%
“…The murine GADD45g promoter shares some structural features with the murine GADD45a promoter, namely Oct and NF-Y putative binding sites. Mutation of these sites in the human GADD45a promoter decreases its basal activity (Hirose et al, 2003). Similarly, we have shown that mutation of either the Oct or NF-Y sites decreases the murine GADD45g promoter basal activity and that expression of Oct-1 and NF-YA increases its activity.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations